2020
DOI: 10.1038/s41598-020-74679-5
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic fungal individuals have the potential to evolve within a single generation

Abstract: Although cells of mushroom-producing fungi typically contain paired haploid nuclei (n + n), most Armillaria gallica vegetative cells are uninucleate. As vegetative nuclei are produced by fusions of paired haploid nuclei, they are thought to be diploid (2n). Here we report finding haploid vegetative nuclei in A. gallica at multiple sites in southeastern Massachusetts, USA. Sequencing multiple clones of a single-copy gene isolated from single hyphal filaments revealed nuclear heterogeneity both among and within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Inter-genetic heterogeneity (mosaic fruiting body) was identified in Armillaria gallica [31] and was suggested to be a contributing factor to the longevity and capacity for continuous growth. A follow-up study of single hyphal filament clones confirmed this inter-strain heterogeneity and uncovered the intra-strain heterogeneity as well [38]. These two types of genetic heterogeneity were suggested to give fungal individuals the potential to evolve within a single generation in response to environmental variation over time and space.…”
Section: Discussionmentioning
confidence: 75%
“…Inter-genetic heterogeneity (mosaic fruiting body) was identified in Armillaria gallica [31] and was suggested to be a contributing factor to the longevity and capacity for continuous growth. A follow-up study of single hyphal filament clones confirmed this inter-strain heterogeneity and uncovered the intra-strain heterogeneity as well [38]. These two types of genetic heterogeneity were suggested to give fungal individuals the potential to evolve within a single generation in response to environmental variation over time and space.…”
Section: Discussionmentioning
confidence: 75%
“…As predicted from theory, (e.g. [7,22], substantial somatic genetic variation has now been identified in clonal plants [3,16], fungi [19], algae [20] and basal invertebrates such as corals [17,18,23]. Some species of fungi and of plants feature much less somatic genetic variation than anticipated, suggesting dedicated mechanisms of keeping somatic mutation rates low and hence, maintaining genome integrity [24,25].…”
Section: Abundant Somatic Genetic Variation In Multicellular Speciesmentioning
confidence: 83%
“…The genomic revolution has yielded a number of relevant data sets that directly address the importance of genetic heterogeneity within organisms at the full genome scale [3,[16][17][18][19][20]. Hence, it is timely to revisit some of the earlier thinking [6,13,14,21] in order to expand the existing population genetic concepts by explicitly acknowledging the interplay between somatically and meiotically generated genetic variation, the distinct levels of selection within and among modules and the potential role of SoGV in adaptation.…”
Section: Somatic Mutations and Within-individual Genetic Heterogeneitymentioning
confidence: 99%
“…As a likely explanation, germinating basidiospores and haploid mycelia on natural substrates that are not easily accessible to them could either be short-lived or become dormant, and then their genetic survival and contribution to new infectious abilities are much dependent on the possibilities to interact and fuse with another compatible haploid partner [ 169 ]. The formation of diploids and haploid mosaic cells can significantly increase phenotypic plasticity in accessing natural resources and adapting to new host environments [ 170 , 171 ]. In fact, in an outdoor inoculation experiment, haploid A. ostoyae isolates were unable to invade seedlings and saplings of Norway spruce, and only diploid mycelia could be recovered from the infected plants, indicating that the colonization of live plant tissues was readily conditioned on a prior onsite diploidization event [ 169 ].…”
Section: Biology and Infection Strategies Of Armillarioid Speciesmentioning
confidence: 99%